MATHEMATICAL MODELING OF TRANSIENT EMERGENCY ELECTROMAGNETIC PROCESSES IN THE SYSTEM OF ELECTRIC TRACTION OF DC - Kostin, M. O.; Myhalichenko, P. Ye. (Science and Transport Progress, 2007)
The article deals with the description of the mathematical model the system traction electric power supply without loading in the short circuit condition and the result of the reserches this accident process. The transition quantity has been defined, and character their change too, which can use for the determined accidents processes.